2002
DOI: 10.4049/jimmunol.169.7.3987
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages, But Not T and B Lymphocytes, Are Critical for Subepidermal Blister Formation in Experimental Bullous Pemphigoid: Macrophage-Mediated Neutrophil Infiltration Depends on Mast Cell Activation

Abstract: Bullous pemphigoid (BP) is a subepidermal blistering disease associated with autoantibodies against two hemidesmosomal proteins, BP180 and BP230. Numerous inflammatory cells infiltrate the upper dermis in BP. We have previously shown by passive transfer studies that Abs to the ectodomain of murine BP180 are capable of triggering blisters in mice that closely mimic human BP. Experimental BP depends on complement activation and neutrophil infiltration. In the present study, we investigated the relative contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 52 publications
1
64
0
2
Order By: Relevance
“…Mice deficient in mast cells, macrophages, or neutrophils are resistant to experimental BP, whereas pathogenic anti-mBP180 antibodies trigger BP skin disease in wild-type mice and mice deficient in T or B, or both T and B cells. Reconstitution with MCs restores the pathogenic activity of anti-mBP180 IgG [82]. It has been shown that complement activation-derived fragments C3a and C5a can induce MC degranulation and that C5 deficiency completely abolishes MC degranulation.…”
Section: Role Of Inflammatory Cellsmentioning
confidence: 97%
“…Mice deficient in mast cells, macrophages, or neutrophils are resistant to experimental BP, whereas pathogenic anti-mBP180 antibodies trigger BP skin disease in wild-type mice and mice deficient in T or B, or both T and B cells. Reconstitution with MCs restores the pathogenic activity of anti-mBP180 IgG [82]. It has been shown that complement activation-derived fragments C3a and C5a can induce MC degranulation and that C5 deficiency completely abolishes MC degranulation.…”
Section: Role Of Inflammatory Cellsmentioning
confidence: 97%
“…Our data suggest that the initiation of PMN infiltration is mediated by resident peritoneal M-dependent production of chemokines previously documented to play a role in orchestrating PMN recruitment in BTG peritonitis (32,33) and in other inflammatory situations (34 -36). MC are also a rich source of proinflammatory and vasoactive mediators and have been documented to play an important role in PMN recruitment during inflammation of the peritoneum (8) as well as other sites such as the skin (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of peritoneal and dermal inflammation have implicated the MC as playing an important role in the initiation of PMN infiltration (8,24). We therefore performed in vitro studies to determine the production of PMN chemokines by BTG-stimulated peritoneal cell populations that had been depleted of M or MC.…”
Section: Chemokine Responses Are M Dependent In Vitromentioning
confidence: 99%
“…The complement system and MC activation are indispensable to the pathogenesis of experimental BP (18,40). Having demonstrated that p38 MAPK activation is also required for disease development, we next investigated the links between complement, MCs, and p38 MAPK.…”
Section: C5ar-mediated P38 Mapk Activation Depends On Mcs-mentioning
confidence: 99%